Results of Application of the New Nutrient Media Set for Cholera Diagnostics within the Frames of the Special Tactical Training Exercises for Specialized Anti-Epidemic Team - A. B. Mazrukho; D. I. Kaminsky; Yu. M. Lomov; N. R. Telesmanich; K. K. Rozhkov; V. D. Kruglikov; E. V. Goncharenko; A. V. Trishina; Yu. M. Pukhov; V. I. Prometnoy; N. L. Pichurina (Проблемы особо опасных инфекций, 2011)
Carried out is approbation of the new nutrient media set for cholera diagnostics on the basis of bakers' yeast pancreatic digest within the frames of the special tactical training exercises for specialized anti-epidemic team (SAET). It is demonstrated that the developed nutrient media set compare favourably with its analogues, commonly used for practical procedures; and its constituent media have a potential to be included into the SAET mobilization reserve.